PROPOSED NEW MARKETING STRATEGY FOR FASHION BAG COMPANY (A CASE STUDY : MAIKA ETNIK BRAND) (The Indonesian Journal of Business Administration, 2019)
Maika Etnik is a brand of fashion bag company located in Cimahi which was founded in 2006. The concept offered in this bag is the uniqueness and strong characteristics of the motifs offered and adapting to the trends in the market related to the ethnic bag. But in terms of sales, Maika Etnik experienced several problems.These problems are analyzed in this study with the aim of finding the root cause of the problems that become obstacles in the business. To overcome the problems that exist in this research, several analyzes are used, STP analysis, 7P Marketing mix, SWOT and TOWS analysis, consumer analysis and competitor analysisMaika Etnik has a problem in the low number of sales caused by several factors related to the 7P aspect of the marketing mix, some of which are the absence of scheduling marketing activities, unorganized marketing activities, lack of innovation and attractive promotions, late in delivery of goods, having no website and offline store that has not been well organized.To be able to increase the number of sales again, then Maika Etnik needs to fix the use of marketing strategy. Improvement related to the 7P aspect of the marketing mix is an important thing, so that improvements can be made optimally by re-analyzing first about the intended STP and the desires of the consumers by distributing questionnaires to 40 respondents. So the solution that can be offered is by creating a new website, using ads on Instagram and Facebook, and consigning to offline stores in Cimahi and its surroundings.Therefore, the design of the new marketing strategy needed to fix all the variables that can affect sales in this case is the 7P marketing mix. To be able to achieve short and long-term, an implementation plan is designed consisting of the implementation schedule, budgeting, and Key Performance Analysis (KPI).Keywords: fashion bags, sales, marketing mix, STP, SWOT